2008
DOI: 10.1007/s10865-008-9159-2
|View full text |Cite
|
Sign up to set email alerts
|

Migraines and meditation: does spirituality matter?

Abstract: Migraine headaches are associated with symptoms of depression and anxiety (Waldie and Poulton Journal of Neurology, Neurosurgery, and Psychiatry 72: 86-92, 2002) and feelings of low self-efficacy (French et al. Headache, 40: 647-656, 2000). Previous research suggests that spiritual meditation may ameliorate some of the negative traits associated with migraine headaches (Wachholtz and Pargament Journal of behavioral Medicine, 30: 311-318, 2005). This study examined two primary questions: (1) Is spiritual medita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(126 citation statements)
references
References 39 publications
3
116
1
2
Order By: Relevance
“…The positive impact of spirituality on pain relates to pain tolerance, headache frequency and mental and spiritual health. Spiritual meditation has been shown to decrease the frequency of migraine headaches and anxiety in individuals [39] . Moreover, the connections between spirituality and physical health in individuals with a chronic disability is another domain that is important to consider.…”
Section: Good Health and Well-beingmentioning
confidence: 99%
“…The positive impact of spirituality on pain relates to pain tolerance, headache frequency and mental and spiritual health. Spiritual meditation has been shown to decrease the frequency of migraine headaches and anxiety in individuals [39] . Moreover, the connections between spirituality and physical health in individuals with a chronic disability is another domain that is important to consider.…”
Section: Good Health and Well-beingmentioning
confidence: 99%
“…Newshan [80] believes it is related to love, connection, meaning, and hope. Studies have found that when people connect to a meaningful source of care, comfort, and love, they are more able to tolerate pain [65][66][67]. Melzack [2] considered the brain an active system that filters, selects, and modulates inputs, and Benedetti [71] has uncovered specific mechanisms at both the biochemical and cellular level for activating the opioid system.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of spiritually meaningful words was described again in 2008 by Wachholtz and Pargament [67] when they reported their effect on 83 participants who met the criteria for vascular headache. The participants were randomly assigned into four groups, Spiritual Meditation, Internal Secular Meditation, External Secular Meditation, and Relaxation.…”
Section: Pain and Spiritual Practicesmentioning
confidence: 95%
See 2 more Smart Citations